Supracondylar humerus fractures in ınfants and early toddlers; characteristics, clinical and radiological outcomes compared with older children - AKGÜLLE, AHMET HAMDİ; ŞAHBAT, YAVUZ; EROL, BÜLENT (My University, 2022)
Background Supracondylar humerus fractures (SCHF) are rarely seen in the youngest age groups (1-3 years). Although there is no difference in the context of treatment options, it has been shown that younger age groups have different characteristics. Few studies have examined toddlers, which have notably different characteristics. This study is the first to report the characteristics, diagnosis, treatment and functional results of SCHF in infants and early toddlers. Methods A retrospective analysis was made of the data of patients younger than 30 months old, who were operated on in our clinic for SCHF between 2012 and 2020 with at least 2 years of follow-up. Patient demographic and surgical data, and the functional and radiological results were documented. Results Evaluation was made of a total of 52 patients comprising 30 females (58%) and 22 males (42%), with a mean age of 20.75 +/- 5.4 months (range, 6-30 months). The injury was in the right elbow in 24 (46%) patients. The mechanism of injury was a fall from an object at home (table, chair, bed, etc.) in 41 (79%) patients. Patients who fell from a height of more than 4 meters had additional injuries (liver laceration, vertebral fracture, etc.). Only 1 patient had anterior interosseous nerve (AIN) damage before the operation, but the final follow-up neurovascular examinations for all patients were normal. The median follow-up period was 4 years (range, 2-7 years). Flynn outcome scores were (88.5%) excellent and variant Hospital for Special Surgery scores were (82.7%) excellent. Conclusions With appropriate treatment of SCHF, the clinical outcomes in infants and early toddlers are excellent. Using a medial pin to achieve and protect stability in this age group does not increase the risk of iatrogenic ulnar nerve damage. Patients younger than 20 months tend to have more varus malalignment but similar functional results.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Cerrahi; Surgery